Development of a financial health indicator based on companies' annual accounts - David Vivet (National Bank of Belgium, 2011)
This document describes the development of a financial health indicator based on companies' financial statements. This indicator is conceived as a weighted combination of variables, which is obtained through a model discriminating between failing firms and non-failing firms. The definition of failure is based on a legal criterion, namely that a company is considered to have failed if it has faced bankruptcy or judicial administration in the past. Based on the model results, companies are positioned in financial health classes, which are intended to be included in the "company files" designed by the Central Balance Sheet Office.
Keywords: C25; G30; G33; 330; Corporate failure; logistic regression; micro-data; financial statements